Integration Of Character Education And Counseling Guidance At Madrasah Ibtidaiyah - Khodijah, Dedek Nursiti; Alif Utama, Mohamad Maulidin (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2025)
This study explores the integration of character education and counseling guidance in Madrasah Ibtidaiyah through library research methodology. The integration model encompasses curricular approaches, school culture development, and collaborative strategies involving teachers, counselors, and parents. Implementation focuses on inculcating religious values, honesty, discipline, responsibility, and tolerance through daily habituation supported by individual and group counseling services. Key challenges include limited professional counselors, dense curriculum burdens, and inconsistent value application across environments. Solutions comprise teacher training programs, dedicated time allocation, parenting initiatives, and effective monitoring systems. The integration proves essential for holistic character formation, combining cognitive value teaching with affective-psychomotor guidance to develop students with noble morals aligned with Islamic values and Pancasila principles, establishing strong character foundations during critical developmental ages 6-12 years